Application of Green Retrofitting Ready Mix Concrete Plant in Indonesia to Increase Financial Benefits and Reduce Environmental Issues: A Case Study - Ardiansyah, Mohammad Kholis; Husin, Albert Eddy; Amin, Mawardi (Balai Besar Standardisasi dan Pelayanan Jasa Pencegahan Pencemaran Industri, 2023)
Currently, the Indonesian government continues to encourage the realization of sustainable development. The green concept is a sustainable development trend in the construction material industry. The concrete industry plays a vital role as a supplier of concrete materials in construction, so its availability is essential. The role of concrete industry itself has a negative impact on the environment. Stakeholders increase the cost of green retrofitting so that the industry or building becomes eco-friendly. The research method was carried out using a process case study, namely, how to implement green retrofitting cost performance in the concrete industry using Value Engineering and Life Cycle Cost Analysis. Theoretically, the research results provide additional knowledge for academics; practitioners can provide problem-solving to get an overview of the implementation of the green concept in the industry regarding the flow of implementation and the benefits of savings in an environmentally friendly production process. The application of value engineering in the green retrofitting of the concrete industry has increased the cost performance of green retrofitting by 8.66% with a return of 3 years and 8 months and increased the functions and benefits of an eco-friendly and sustainable concrete industry